Incorrect Strategies Developed by Seventh- Grade Students to Solve Proportional Reasoning Problems - Meltem Gulsum KARLI; Esra YILDIZ (Anı Publishing, 2022)
This study was conducted to determine the incorrect strategies developed by seventh-grade students to solve problems that require proportional reasoning and evaluate their solutions according to SOLO Taxonomy. This two-stage case study was conducted in a public school in the Central Black Sea region. The Proportional Reasoning Skill Test was administered to 33 seventh-grade students in the first stage. In the second stage, semi-structured interviews were held with 10 students by determining the 5 problems that students made mistakes in most. The students developed 5 different incorrect strategies when solving problems requiring proportional reasoning: additive relationships, data neglect, using numbers and no content, giving an emotional response, and failure to identify non-proportional situations. Students had difficulty identifying non-proportional situations and established additive relationships in problems requiring multiplicative relationships. Also, the levels of the participants were examined with the SOLO Taxonomy Rubric developed for proportional reasoning skills. Accordingly, the students with a high level of proportional reasoning were at abstract and relational structure levels, whereas those with moderate scores were at uni-structural and multi-structural levels. The students with low scores had low-level skills according to SOLO Taxonomy criteria.